INNOVATION IN THE MANAGEMENT OF JOGOKARIYAN MOSQUE FOR ISLAMIC STUDIES IN THE DIGITAL ERA - Pradipa, Rafi; Na’imah, Na’imah; Kiram, Syaiful; Auf, Muhammad Azmi; Huda, Syariful (Idaarah: Jurnal Manajemen Pendidikan, 2025)
This study was conducted to find the form of innovation of the Jogokariyan Mosque management in Islamic studies in the digitalization era, the supporting factors for implementing innovation, and its impact or implications for society. This type of research was conducted using a descriptive qualitative method. To obtain data for this study, the researcher came directly to the location, namely the Jogokariyan Mosque in Yogyakarta. To get an overview of the object, the researcher interviewed several components in the mosque, observation, and documentation. The results of this study show 1) Jogokariyan Mosque Integrates Technology in Islamic Preaching & Study Activities: In the form of Using Social Media Including; Instagram, Facebook, Jogokariyan Mosque YouTube channel, WhatsApp, Tiktok. 2) Good mosque management, the totality of the administrators to prosper the Jogokariyan Mosque, Facilities and infrastructure that make the congregation comfortable, The prosperity of the mosque which also has an impact on Islamic study activities at the Jogokariyan mosque, Support from various parties who help each other. 3) Facilitate the congregation to follow Islamic studies from any location and increase the number of congregation participation, Increase the involvement of the younger generation who are more familiar with digital technology, Studies conducted online contain interesting themes that are happening in society so that the community can find the best solution, Provide facilities and understanding to the community to be able to follow various studies that exist including; Subuh Study, Ummida Study, Tuesday Night Study, Wednesday Night Study, Ahad Legi Study, Aisyiyah Study.